Gamification in Duolingo App on Improving English Listening Proficiency of Junior High School Students - Rosyidah, Umniyah Juman; Dewanti Laksmi, Ekaning; Anugerahwati, Mirjam (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
Gamification is considered as a strategy to involve students in solving problems related to learning English, rather than playing games. Duolingo, an application that uses gamification, is suitable for junior high school students as a formal classroom setting in English learning. This study aimed at investigating whether the use of gamification in Duolingo App can improve the listening proficiency of junior high school students in English. This research uses quasi-experimental design with quantitative approach. The data is collected using test and observation and analyzed using SPSS 26 App. The results show that the sig. (2 tailed) indicated is 0.002 meaning that there is difference between post-test of experiment class and control class. It is concluded that gamification in Duolingo app affects English listening proficiency of junior high school students. Hence, Duolingo App has the potential to serve as a valuable tool for educators to enhance their students' listening skills. Additionally, gamification can form the foundation for the development of technological learning resources. However, this study has some limitations, and further research involving different educational levels, media, and longer experiment duration is necessary to obtain detailed and reliable results that can be applied to the broader population.